Literature Study of Political Communication Based on Politic Identity and Symbolic Interactionism: The Role of Middle Class in Information of Democratization - Muhamad Ferdy Firmansyah; Apip Kurniawan (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2021)
Political communication is a very important part of the development of politics in Indonesia. Every general election will be filled with various kinds of propaganda targeting various segments of society. Identity politics is a form of public political expression that uses slogans that contain every political message. The characteristics of the use of identity politics can be identified through the concept of symbol interactionism. This study uses a qualitative approach with literature studies and focuses on analyzing the relationship between identity politics by identifying it with the concept of symbol interactionism and connecting it with Acemoglu's three-class model with a focus on middle-class voters. The purpose of this study is to find out the impact of the movement of using identity politics targeting the lower middle class on efforts to mature democratization in political communication. This research will combine the phenomenon of identity politics with symbol interactionism to a simplified pattern of political communication. The results obtained are the phenomenon of identity politics which is identified by symbol interactionism and mathematical modeling is formed as an explanation for the classification of each phenomenon. The classification of each phenomenon found in this study includes elements of (1) revolution, (2) repression, and (3) coup. By referring to the literature associated with the identity politics model in symbol interactionism, it is found that the role of the middle class is very small in the revolution, very high for starting repression, and very unlikely to start a coup.